Two Theological Movements in India That Complicate Western Reformed Identities - Schweitzer, Don (Toronto journal of theology, 2012)
This essay examines how Indian Christian theology and Dalit theology, products of the contextualization of Christianity in India, complicate Western Reformed Christian identities. The former has introduced elements of Hinduism into Christian thought there. This raises questions about what is Christian and what Western in some Western Reformed theologies. This conversation is further complicated by Dalit theology, which critiques Indian Christian theologies for overlooking caste oppression. This paper invokes the reign of God and the preferential option for the poor as principles that can guide Western Reformed theologies in responding to the challenges raised by these two theological movements in India.